2005
DOI: 10.3748/wjg.v11.i36.5659
|View full text |Cite
|
Sign up to set email alerts
|

Screening of hepatocyte proteins binding to F protein of hepatitis C virus by yeast two-hybrid system

Abstract: AIM:To investigate the biological function of F protein by yeast two-hybrid system. METHODS:We constructed F protein bait plasmid by cloning the gene of F protein into pGBKT7, then recombinant plasmid DNA was transformed into yeast AH109 (a type). The transformed yeast AH109 was mated with yeast Y187 (α type) containing liver cDNA library plasmid in 2×YPDA medium. Diploid yeast was plated on synthetic dropout nutrient medium (SD/-Trp-Leu-HisAde) containing X-α-gal for selection and screening. After extracting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Whereas the majority of the described interactions are for bacterial proteins, there are a few viral proteins that have been shown to interact with human VN, including the HIV gp120/160 protein (34,35) and the hepatitis C virus (HCV) F protein (36). This is the first study to report the interaction of DENV NS1 with VN as a complement evasion strategy.…”
Section: Discussionmentioning
confidence: 90%
“…Whereas the majority of the described interactions are for bacterial proteins, there are a few viral proteins that have been shown to interact with human VN, including the HIV gp120/160 protein (34,35) and the hepatitis C virus (HCV) F protein (36). This is the first study to report the interaction of DENV NS1 with VN as a complement evasion strategy.…”
Section: Discussionmentioning
confidence: 90%
“…In fact, recent studies indicated that ARFP is an unstable protein that associates with the endoplasmic reticulum [13] and may play a role in the regulation of gene expression, cell signaling and apoptosis [14][15][16][17], as well as in altering immune responses [18]. These potential properties of the ARFP have attracted recently much attention and intensified the studies of its features.…”
mentioning
confidence: 96%
“…These results implicate core11 in functions previously attributed to core protein, in the pathogenesis of chronic infection and cellular transformation. Guo et al also identified genes transactivated by core11/F and involved in metabolism, cell cycle regulation and cell apoptosis (97).…”
Section: Functional Properties Of Core11 Proteinsmentioning
confidence: 99%
“…Dou et al searched for changes in gene expression profile in human hepatoma Huh7 cells stably producing core11/F in microarray and semiquantitative RT-PCR analyses (98), whereas Guo et al screened for genes differentially expressed in the presence and absence of core11/F by suppression subtractive hybridization (97). Guo et al identified 36 interacting partners, 34 of which had known functions closely related to lipid and carbohydrate metabolism, protein synthesis and transport, immunoregulation or the occurrence and development of tumors (97). However, these data remain to be confirmed.…”
Section: Functional Properties Of Core11 Proteinsmentioning
confidence: 99%